2016
DOI: 10.1002/bio.3233
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic andin silicostudy of binding mechanism of cynidine‐3‐O‐glucoside with human serum albumin and glycated human serum albumin

Abstract: The drug-serum albumin interaction plays a dominant role in drug efficacy and disposition. The glycation of serum albumin that occurs during diabetes may affect its drug-binding properties in vivo. In order to evaluate the interactivity characteristics of cyanidin-3-O-glucoside (C3G) with human serum albumin (HSA) and glycated human serum albumin (gHSA), this study was undertaken using multiple spectroscopic techniques and molecular modeling analysis. Time-resolved fluorescence and the thermodynamic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…23 HSA is composed of 585 residues with dominant α-helix conformation, three structural domains (I-III), and numerous efficient drug binding sites. 24 HSA has been widely used as one of the most extensively studied proteins, not only because of its biomedical significance, low cost, availability, and wide approval in the pharmaceutical industry, but also due to its ligand-binding properties. 25,26 The white blood cells (WBCs) and SH-SY5Y cells 27,28 are highly sensitive and commonly used for assessing the NP toxicity and their anticancer effects, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…23 HSA is composed of 585 residues with dominant α-helix conformation, three structural domains (I-III), and numerous efficient drug binding sites. 24 HSA has been widely used as one of the most extensively studied proteins, not only because of its biomedical significance, low cost, availability, and wide approval in the pharmaceutical industry, but also due to its ligand-binding properties. 25,26 The white blood cells (WBCs) and SH-SY5Y cells 27,28 are highly sensitive and commonly used for assessing the NP toxicity and their anticancer effects, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence spectroscopy is commonly used to characterize the interaction of fluorescent macromolecular proteins with other small molecule ligands and to determine the quenching mechanism of complexes by fluorescence temperature change experiments [19,20]. Thence, the Stern–Volmer equation, Equation (1) was used for analysis [21]:F0/normalF=1+Kqτ0[Q]=1+KSV[Q]…”
Section: Resultsmentioning
confidence: 99%
“…The results were shown in Figure 3A,B, and the calculation data was shown in Table 1. It could be seen in Table 1 that the K q value during the reaction was much larger than the maximum diffusion collision quenching constant value (2.0 × 10 10 L/mol/s) [21]. Therefore, the quenching mechanism existing in the process of determining the binding of TF to HSA and GHSA were a static quenching mechanism for the formation of a ground state complex [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of the α‐helix percentage indicated that the aurantio‐obtusin bound with the amino acid residues of the main polypeptide chain and partly destroyed the hydrogen bonding networks of HSA. It is known that the α‐helix is relevant to the hydrophobic property, the conversions of α‐helix to β‐sheet structures can occur by the insertion of aurantio‐obtusin molecules into the hydrophobic surface of HSA, and the interaction enhanced the solvation effect between HSA and the water molecules, causing the protein side chains to associate with water molecules by hydrogen bonding and Van der Waals forces, decreasing the percentage of α‐helix …”
Section: Resultsmentioning
confidence: 99%